Sequestration of P fractions in the soils of an incipient ferralisation chronosequence on a humid tropical volcanic island - Chiu, Chih‑Yu; Baillie, Ian C.; Jien, Shih‑Hao; Hallett, Liam; Hallett, Stephen (Springer, 2021)
Background: Phosphorus (P) is the limiting nutrient in many mature tropical forests. The ecological significance of declining P stocks as soils age is exacerbated by much of the remaining P being progressively sequestered. However, the details of how and where P is sequestered during the ageing in tropical forest soils remains unclear. Results: We examined the relationships between various forms of the Fe and Al sesquioxides and the Hedley fractions of P in soils of an incipient ferralitic chronosequence on an altitudinal series of gently sloping benches on Green Island, off the southeastern coast of Taiwan. These soils contain limited amounts of easily exchangeable P. Of the sesquioxide variables, only Fe and Al crystallinities increased significantly with bench altitude/soil age, indicating that the ferralisation trend is weak. The bulk of the soil P was in the NaOH and residual extractable fractions, and of low lability. The P fractions that correlated best with the sesquioxides were the organic components of the NaHCO3 and NaOH extracts. Conclusions: The amorphous sesquioxides, Feo and Alo, were the forms that correlated best with the P fractions. A substantial proportion of the labile P appears to be organic and to be associated with Alo in organic-aluminium complexes. The progression of P sequestration appears to be slightly slower than the chemical and mineralogical indicators of ferralisation.
Keywords: Soil P; Hedley fractions; Sesquioxides; Chronosequence; Taiwan